SPILLOVER EFFECTS FROM FOREIGN DIRECT INVESTMENT TO LOCAL SMES. AN EMPIRICAL STUDY - MARINESCU, Nicolae (Studia Universitatis Babeș-Bolyai Negotia, 2016)
Foreign direct investment (FDI) is known for having a diversified impact on the host economy. Some of its potential outcomes are represented by spillovers to local enterprises. The aim of this paper is to analyze the spillover effects of FDI in Romania to local small and medium-sized enterprises (SMEs) by means of a case study. The present research is an empirical study and, as such, contributes insights into the literature on FDI in Central and Eastern European countries (CEECs), providing additionally a link between FDI and SMEs. The paper starts by reviewing the literature on FDI with regard to spillover and linkage effects on SMEs in the local economy. The second section focuses on the particular linkages between FDI and SMEs and their characteristics in the CEECs and Romania. The third section of the paper investigates the case of a large industrial foreign affiliate in Brasov County and the way it contributed to the performance of local SMEs in terms of turnover and employee growth. Several results of the empirical study are highlighted. The final section presents some conclusions and pinpoints the contribution of this study to the existing literature.